PENGAWASAN LIMBAH CAIR RUMAH SAKIT OLEH BADAN LINGKUNGAN HIDUP KOTA PEKANBARU 2014-2015 - Gunawan, Marhta; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Supervisory control of hospital sewage in the city of Pekanbaru aims to identify and anallyze the supervisory control of hospital sewage in the city of Pekanbaru. In fact there are many hospital that have not complied with such as have no means of wastewater treament but get permission. Study of phenomena, the formulatioon of the problem of this research is how the supervision and control of hospital sewage in the city of Pekanbaru and the factors that influence the supervision and control of hspital sewage in the city of Pekanbaru. This study uses the theory of Sukanto.This study used a descriptive analysis method. Data collection technique is the observation, interviews, and library research. Key informents of this study is the Badan Lingkungan Hidup In Pakanbaru, the hospital and the community.The results showed that not maximal supervisory control of hospital sewage in the city of Pekanbaru is carried out by the Badan Lingkungan Hidup in Pekanbaru. It looks there are still hospitals that do not have control permit process wastewater and waste properly. As well as not optimal implementation factors that influence the Supervision and Control of hospital sewage in the city of Pekanbaru is the lack of qualified human resources and experts to go into the field so there are still many hospitals that have not done direct monitoring. As well as the need to hold socialization to the communityKeywords : Liquid waste, Badan Lingkungan Hidup and control.